An Alpha and Theta Intensive and Short Neurofeedback Protocol for Healthy Aging Working-Memory Training - Reis, Joana; Portugal, Ana Maria; Fernandes, Luís; Afonso, Nuno; Pereira, Mariana; Sousa, Nuno; Dias, Nuno S. (Frontiers in Aging Neuroscience, 2016)
The present study tested the effects of an intensive and short alpha and theta neurofeedback (NF) protocol in working memory (WM) performance in a healthy elder population and explored the effects of a multimodal approach, by supplementing NF with cognitive tasks. Participants were allocated to 4 groups: neurofeedback (NF N = 9); neurofeedback supplemented with cognitive training (NFCT N = 8); cognitive training (CT N = 7) and sham neurofeedback (Sham-NF N= 6). The intervention consisted in 30-minute sessions for 8 days. The NF group presented post intervention increases of alpha and theta relative power as well as performance in the matrix rotation task. In addition, a successful up training of frontal theta showed positive correlation with an improvement of post-training alpha and a better performance in the matrix rotation task. The results presented herein suggest that an intensive and short NF protocol enables elders to learn alpha and theta self-modulation and already presents moderate improvements in cognition and basal EEG. Also, both CT and NFCT groups showed moderate performance gains on the cognitive tasks used during the training sessions but no clear improvements on neurophysiology and behavioral measurements were observed. This study represents a first attempt to study the effects of an intensive and short NF protocol in WM performance of elders. The evidence presented here suggests that an intensive and short NF intervention could be a valid alternative for introduction of older populations to NF methodologies.